The problem of resistance of microorganisms ‒ challenge to humanity - N. О. Vrynchanu; T. A. Bukhtiarova (The State Expert Center of the Ministry of Health of Ukraine, 2021)
One of the XXI century public health urgent problems is the antibiotic therapy effectiveness decrease as a result of microorganisms resistant strains emergence and spread. The aim of review is the antibiotic resistance causes and medicines effects on the formation of microorganisms resistance to antibiotics modern data analysis. Сontent analysis, bibliosemantic, scientometric and systemic methods was used in the work. Our analysis showed that at present the question of the non-antimicrobial medicines role in the antibiotic resistance formation remains open. Medicines of different pharmacotherapeutic groups are able to demonstrate antimicrobial activity, realizing both by microorganisms inhibition and their growth stimulation. The problem of such medicines influence on the antibiotics specific activity needs additional investigation in order to possible antagonistic effects identification. Special attention deserves the question of non-antimicrobial medicines subinhibitory concentrations accumulation in the environment in view of their ability to stimulate biofilms formation. Antibiotic resistance is a global problem; in order to its spread repression and antimicrobial therapy effectiveness preservation, it is necessary to establish all its possible causes and contributing factors. Non-antimicrobial medicines role in the resistance formation detection is one of the ways to control these processes. Such complex measures allow preserving the existing antimicrobial preparations effectiveness for the future generations.